13C and 15N solid-state NMR studies on albendazole and cyclodextrin albendazole complexes. (5th June 2015) - Ferreira, M. João G.; García, A.; Leonardi, D.; Salomon, Claudio J.; Lamas, M. Celina; Nunes, Teresa G.
Highlights: Spray-dried mixtures of albendazole and cyclodextrins are studied by solid-state NMR. Different stable complexes are identified depending on the cyclodextrin substituent. Influence of cyclodextrins on albendazole solubility enhancement is explained. Abstract: 13 C and 15 N solid-state nuclear magnetic resonance (NMR) spectra were recorded from albendazole (ABZ) and from ABZ:β-cyclodextrin, ABZ:methyl-β-cyclodextrin, ABZ:hydroxypropyl-β-cyclodextrin and ABZ:citrate-β-cyclodextrin, which were prepared by the spray-drying technique. ABZ signals were typical of a crystalline solid for the pure drug and of an amorphous compound obtained from ABZ:cyclodextrin samples. Relevant spectral differences were correlated with chemical interaction between ABZ and cyclodextrins. The number and type of complexes revealed a strong dependence on the cyclodextrin group substituent. Solid-state NMR data were consistent with the presence of stable inclusion complexes.